Features of randomised trials designed by the NPEU Perinatal Trials Service during Adrian Grant's directorship - Diana Elbourne (BMC, 2018)
Abstract Adrian Grant pioneered methodological innovations in the randomised trials organised by the Perinatal Trials Service established at the national Perinatal Epidemiology Unit in Oxford, UK. This Commentary discusses these innovations, and shows the wide range of trials designed under his directorship.